2023
DOI: 10.3389/fpsyg.2023.1081467
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Changes in defense mechanisms, personality functioning, and body mass index during psychotherapy with patients with anorexia nervosa

Abstract: Eating disorders (EDs) are difficult to treat in psychotherapy due to their pervasive symptomatology and frequent and rapid relapses. Restrictive anorexia nervosa (AN) is the most challenging ED, often associated with severe physical and mental conditions. Perceived as an ego-syntonic syndrome that somehow protects the patient from a number of developmental tasks, treating AN requires extensive multidisciplinary long-term intervention. As with other emotion regulation strategies, defense mechanisms mediate an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In summary, these findings suggest that particular attention should be paid to adaptation strategies such as coping and defense mechanisms, which play a key role in promoting therapeutic compliance and psychological well-being (Conversano et al ., 2023 ). Tailoring therapeutic intervention based on improving individual’s adaptive responses to stressful disease-related consequences could effectively enhances patient’s mental health and overall higher QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these findings suggest that particular attention should be paid to adaptation strategies such as coping and defense mechanisms, which play a key role in promoting therapeutic compliance and psychological well-being (Conversano et al ., 2023 ). Tailoring therapeutic intervention based on improving individual’s adaptive responses to stressful disease-related consequences could effectively enhances patient’s mental health and overall higher QoL.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals have the ability to change stressful situations into safe ones, maintain composure in the face of challenges, making problem confrontation not a difficult task. They can also accurately identify efficient and situation-specific coping mechanisms to reduce internal anxiety (Brody & Carson, 2012;Conversano et al, 2023). Individuals with positive temporal attitudes are optimistic, focusing on positives rather than dwelling on negatives, regretting the past, or fearing the future, thus preparing them to accept reality and live in the present.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in object relations undermine the foundations of personal security and lead to increased vulnerability to grief (Ahadian fard et al, 2017;Orang et al, 2018). Numerous studies have confirmed the hypothesis that mental health is significantly related to defense mechanisms (Besharat, 2008;Blanco et al, 2023;Brockman et al, 2016;Brody & Carson, 2012;Conversano et al, 2023;Cramer, 1987Cramer, , 2002Giuseppe & Perry, 2021;Jamilian et al, 2014;Jun et al, 2015;Lee et al, 2020;Lotfi-Hajilo et al, 2017;Mesgarian et al, 2017;Poshtareh et al, 2023;Rubino et al, 2007). More mature defenses enable an individual to act more adaptively and with fewer anxiety symptoms in anxiety-provoking situations, such as social scenarios, while immature defense mechanisms lead to the emergence of anxiety and avoidance in these situations (Jamilian et al, 2014;Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The defense mechanism hierarchy incorporates three overarching defense categories: Mature defense mechanisms that are the most adaptive, neurotic defenses, which reflect mental inhibition, and Immature defenses, that involve more distortion of inner and outer reality (Perry, 2014 ). Furthermore, the immature category can be divided into depressive and non-depressive defenses (Perry et al ., 2020 ), and there is some evidence indicating that depressive defenses are especially strongly associated with mental health symptoms and psychopathology (Maffei et al ., 1995 ; Høglend & Perry, 1998 ; Conversano et al ., 2023 ). See Supplementary Figure 1 for a review of the DMRS-based defense hierarchy.…”
Section: Introductionmentioning
confidence: 99%